LINGUISTIC AND POETIC INTERPRETATION OF COLORS AND NATURAL LANDSCAPES IN THE SYSTEM OF ARTISTIC MEANS OF EXPRESSION - Mahzuna Qodiriy (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article investigates the linguistic and poetic functions of artistic expressive means in literary discourse, focusing on color symbolism (chromatism) and landscape representation as key components of imagery. Drawing on approaches from linguopoetics and cognitive linguistics (Lakoff and Johnson, 1980; Stockwell, 2002), the study analyzes how color terms and natural descriptions contribute to meaning construction and aesthetic effect in literary texts. Special attention is given to the psychological impact of color vocabulary and its role in evoking emotional and evaluative responses in readers. The research also examines the principle of psychological parallelism, where elements of nature mirror the inner states of characters, enhancing narrative depth and interpretative complexity. Based on examples from the Uzbek literary tradition, the article demonstrates how metaphors, epithets, and symbolic landscapes function as semiotic tools that shape reader perception and conceptualization. Overall, color and landscape imagery are interpreted as cognitive and stylistic mechanisms that enrich textual expression and reflect culturally embedded ways of seeing the world.